Features of the formation of the hospitality industry of the Vinnytsia region - R. Lopatiuk (Kazimierz Wielki University, 2022)
In Ukraine, there are certain limiting problems in the field of tourism positive transformation of this type of activity. Hospitality establishments of the Vinnytsia region are analyzed in the article. It was revealed that with the help of a cluster form of enterprise organization, it is possible to improve the management mechanism, specialization, cooperation, rationally use territorial division and resources. Examples of improving the standard of living of the population with the help of a cluster mechanism are given, which increases the competitiveness of businesses located in a certain territory, supports an effective business climate and ensures the transition to the integrated use of the potential of the entire state.